POLITIK HUKUM PERLINDUNGAN HAK PEKERJA PASCA UNDANG-UNDANG NOMOR 6 TAHUN 2023 TENTANG CIPTA KERJA: STUDI PRAKTIK ADVOKASI SERIKAT PEKERJA DI KABUPATEN BEKASI - Hadi Maryono; Hery Chariansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation into Law has fundamentally transformed Indonesia’s labour law system, particularly with respect to employment relationships, termination of employment, wages, outsourcing, and the protection of workers’ rights. These legal reforms have generated continuing debate regarding the balance between promoting investment and safeguarding workers’ rights. This study aims to analyse the legal politics of workers’ rights protection following the enactment of Law Number 6 of 2023 and to examine its implementation through labour union advocacy practices in Bekasi Regency. The research employs a normative-empirical legal method using statutory, conceptual, and case approaches. Primary data were obtained through interviews with the Bekasi Regency Manpower Office and documentation of advocacy practices conducted by FSP LEM SPSI, while secondary data were collected from legislation, Constitutional Court decisions, books, and scholarly journal articles. The findings indicate that post-Job Creation labour policy promotes greater labour market flexibility to support investment while remaining subject to constitutional guarantees of workers’ rights. Labour union advocacy through collective bargaining agreements, settlement of rights disputes, resolution of termination of employment disputes, and industrial relations mediation has proven effective in strengthening workers’ rights protection. The novelty of this study lies in integrating legal politics analysis with empirical evidence derived from labour union advocacy practices in the Bekasi industrial area, providing a comprehensive understanding of the implementation of workers’ rights protection after the enactment of Law Number 6 of 2023.